Papaya Development Model As A Competitive Local Superior Commodity - Sukmawani, Reny; Haeruman, Maman; Sulistyowati, Lies; Perdana, Tommy (Universitas Muhammdaiyah Surakarta, 2014)
The aim of this research is to study the comparative advantage and papaya competitive and to design its development model by using the approach of local base agriculture development. This research uses survey method. The resulting research shows that papaya is a base commodity that has comparative advantage and competitive. The development papaya in the district of Sukabumi is quite good bases on eight superior creations. But in order to be the main sector in economic development and has a competition, the development of papaya must concern to its influence factors. In supporting papaya development as a competitive local superior commodity, it needs to be done some efforts are as follows: (1) increase a skillful worker; (2) improve business management; (3) increase papaya productivity by using technology and study papaya planted technology in specific local superior commodity; (4) develop the involvement of the business relation; (5) provide market information and information technology network; and (6) improve infrastructures.